Epstein-Barr virus perpetuates B cell germinal center dynamics and generation of autoimmune-associated phenotypes in vitro - SoRelle, Elliott D.; Reinoso-Vizcaino, Nicolás M.; Horn, Gillian Q.; Luftig, Micah A. (Frontiers in Immunology, 2022)
Human B cells encompass functionally diverse lineages and phenotypic states that contribute to protective as well as pathogenic responses. Epstein-Barr virus (EBV) provides a unique lens for studying heterogeneous B cell responses, given its adaptation to manipulate intrinsic cell programming. EBV promotes the activation, proliferation, and eventual outgrowth of host B cells as immortalized lymphoblastoid cell lines (LCLs) in vitro, which provide a foundational model of viral latency and lymphomagenesis. Although cellular responses and outcomes of infection can vary significantly within populations, investigations that capture genome-wide perspectives of this variation at single-cell resolution are in nascent stages. We have recently used single-cell approaches to identify EBV-mediated B cell heterogeneity in de novo infection and within LCLs, underscoring the dynamic and complex qualities of latent infection rather than a singular, static infection state. Here, we expand upon these findings with functional characterizations of EBV-induced dynamic phenotypes that mimic B cell immune responses. We found that distinct subpopulations isolated from LCLs could completely reconstitute the full phenotypic spectrum of their parental lines. In conjunction with conserved patterns of cell state diversity identified within scRNA-seq data, these data support a model in which EBV continuously drives recurrent B cell entry, progression through, and egress from the Germinal Center (GC) reaction. This “perpetual GC” also generates tangent cell fate trajectories including terminal plasmablast differentiation, which constitutes a replicative cul-de-sac for EBV from which lytic reactivation provides escape. Furthermore, we found that both established EBV latency and de novo infection support the development of cells with features of atypical memory B cells, which have been broadly associated with autoimmune disorders. Treatment of LCLs with TLR7 agonist or IL-21 was sufficient to generate an increased frequency of IgD-/CD27-/CD23-/CD38+/CD138+ plasmablasts. Separately, de novo EBV infection led to the development of CXCR3+/CD11c+/FCRL4+ B cells within days, providing evidence for possible T cell-independent origins of a recently described EBV-associated neuroinvasive CXCR3+ B cell subset in patients with multiple sclerosis. Collectively, this work reveals unexpected virus-driven complexity across infected cell populations and highlights potential roles of EBV in mediating or priming foundational aspects of virus-associated immune cell dysfunction in disease.